Strong humoral immune responses against SARS-CoV-2 Spike after BNT162b2 mRNA vaccination with a 16-week interval between doses - Tauzin, Alexandra; Gong, Shang Yu; Beaudoin-Bussières, Guillaume; Vézina, Dani; Gasser, Romain; Nault, Lauriane; Marchitto, Lorie; Benlarbi, Mehdi; Chatterjee, Debashree; Nayrac, Manon; Laumaea, Annemarie; Prévost, Jérémie; et al. (Cell host & microbe, 2022)
The standard regimen of the BNT162b2 mRNA vaccine for SARS-CoV-2 includes two doses administered three weeks apart. However, some public health authorities spaced these doses, raising questions about efficacy. We analyzed longitudinal humoral responses against the D614G strain and variants of concern for SARS-CoV-2 in a cohort of SARS-CoV-2-naive and previously infected individuals who received the BNT162b2 mRNA vaccine with sixteen weeks between doses. While administering a second dose to previously infected individuals did not significantly improve humoral responses, these responses significantly increased in naive individuals after a 16-week spaced second dose, achieving similar levels as in previously infected individuals. Comparing these responses to those elicited in individuals receiving a short (4-week) dose interval showed that a 16-week interval induced more robust responses among naive vaccinees. These findings suggest that a longer interval between vaccine doses does not compromise efficacy and may allow greater flexibility in vaccine administration.